ANALISIS KINERJA BERBASIS MOTIVASI PEGAWAI MADRASAH ALIYAH NEGERI 4 SLEMAN - muh bahrul anwar (UPAJIWA, 2020)
This study aims to analyze the influence of leadership style variables, organizational culture on employee motivation and performance. This research was conducted at MAN 4 Sleman. The number of samples set is 54 respondents with sampling using the census method. Measurements in the questionnaire using a Likert scale. Data is processed using Partial Least Squares (PLS) analysis, which is SEM with SmartPLS 3.0 software. The results showed that the Leadership Style had a positive and significant effect partially on employee motivation, this was proven by the P-Value value of 0.001 and the parameter coefficient value was 0.378 so that it supports the first hypothesis. Organizational culture has a positive and significant effect partially on Employee Performance, this is evidenced by the P-Value value of 0.034 and the parameter coefficient value of 0.233 so that it supports the second hypothesis. Organizational culture has a positive and significant effect partially on Motivation, this is evidenced by the P-Vaue value of 0.015 and the parameter coefficient value of 0.347 so it supports the third hypothesis, Organizational Culture has a positive and significant influence partially on employee performance, this is evidenced by P-Vaue value is 0.035 and the parameter coefficient value is 0.346 so it supports the fourth hypothesis, Motivation has a positive and significant effect partially on employee performance, this is evidenced by the P-Vaue value of 0.028 and the parameter coefficient value is 0.362 thus supporting the fifth hypothesis. The results of the path analysis show that the leadership style has a positive and significant effect partially on motivation by 0.378, while on employee performance by 0.233, Organizational Culture has a positive and significant effect partially on motivation by 0.347, while on employee performance is 0.346 and Motivation has a positive effect and partially significant towards employee performance of 0.362